A ball-bearing structured triboelectric nanogenerator for nondestructive damage and rotating speed measurement. (25th January 2016) - Li, Xiao Hui; Han, Chang Bao; Jiang, Tao; Zhang, Chi; Wang, Zhong Lin
Abstract: A ball-bearing structure based triboelectric nanogenerator (B-TENG) with interdigitative-electrodes was developed that can not only collect energy from rotational kinetic energy, but also serve as a self-powered and multifunctional sensor. The B-TENG relies on the rolling electrification between PTFE balls on Cu interdigitative-electrodes, which delivers an open-circuit voltage of ∼40 V and a short-circuit current of ∼1.2 μ A at a rotating speed of 300 rpm for 4 mm PTFE balls. Using the output signals of B-TENG, a nondestructive detection for the damage of PTFE balls was realized without demounting the bearing. Besides, based on the periodic signals produced from B-TENG, the rotation speed of ball-bearing can be obtained according to the time difference between several cycles.